Nilai Etik Hukum Islam Dalam Mengkonstruksi Hak Egaliter Pendidikan Perempuan - Minarti, Sri (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Islamic law represent holy comands of Allah arranging all life aspect every Moslem, and cover items punish purely and also items of spiritual religious. He have the nature of elastic fixed hold on to its it's spirit that is and egaliter of monothoistik and also have character of egaliter, don't rasial, not feodal and not patriarkhal. Thereby, education of Islam which dimiciling it's equal to Islam law at theoretical framework and also aplicative cannot discharge it his spirit that is and egaliter of monothoistik. Principal of education of Islam which this egaliter which later have to be developed by at this contemporary education era, backward cause of moslem after glorious so much year in consequence of left behind his of education of woman.